Understanding Long-Term Impacts in the Forest Sector : Predictive Proxy Indicators - Miller, Daniel C. (World Bank, Washington, DC, 2016)
The international development community is increasingly demanding better evidence on the effectiveness of policies and programs across different sectors. The forest sector is no exception. Governments and donor agencies explicitly seek to link investment to proven impact. Yet the evidence base necessary to inform interventions in the forest sector that can successfully enhance the livelihoods of the forest-dependent poor, foster economic growth, reduce emissions from deforestation and degradation, and conserve forest biodiversity remains weak. There is a particular need to identify robust indicators to track and assess the impacts of forest-related investments. The Independent Evaluation Group (IEG) 2013 review of the Forests Strategy of the World Bank, the largest multilateral funding source in the sector, and the subsequent Committee on Development Effectiveness (CODE) report highlighted this need. The IEG recommended the development of outcome indicators on sustainable forest management to track progress across the World Bank’s Forests Strategy. The 2013 CODE report highlighted the imperative to develop short-term proxy indicators for long-term impacts in the forest sector. To date, however, there is little systematic knowledge on the availability of such predictive proxies in the sector, what form they should take, and the conditions under which they are effective. This PROFOR-financed study responds to this gap in knowledge and to broader demand from donors, government agencies, and implementing organizations to develop robust, yet practical means to better understand the impacts of forest sector investments. It focuses in particular on potential predictive proxies for longer-term term outcomes and suggests that such indicators do in fact exist. The report identifies a set of theory-based predictive proxy indicators (PPIs) relevant to one or more overarching development objectives: poverty reduction and economic growth, biodiversity conservation, climate change mitigation and adaption, and good governance.